2009
DOI: 10.1016/j.bcp.2009.02.020
|View full text |Cite
|
Sign up to set email alerts
|

In vitro studies on the metabolism of trabectedin (YONDELIS®) in monkey and man, including human CYP reaction phenotyping

Abstract: Trabectedin (YONDELIS) is a potent anticancer agent which was recently approved in Europe for the treatment of soft tissue sarcoma. The drug is currently also in clinical development for the treatment of ovarian carcinoma. In vitro experiments were conducted to investigate the hepatic metabolism of [(14)C]trabectedin in Cynomolgus monkey and human liver subcellular fractions. The biotransformation of trabectedin was qualitatively similar in 12,000 x g supernatants of both species, and all human metabolites wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 29 publications
0
20
1
1
Order By: Relevance
“…Vermier et al (2009) [358] recently extensively studied the metabolism of trabectedin in monkey and human liver microsomes. The authors found that the metabolite profiles of trabectedin at 5 M in Cynomolgus monkey and human liver microsomes were similar using 14 C-radiolabeled drug, although there was a higher abundance of the M4a/4b and M8b/8c metabolites in monkey fractions than in human fractions, suggesting a more active biotransformation of trabectedin via N-demethylation (to form M8b) and/or via demethylation with additional mono-oxidation (to form M4b), di-oxidation (to form M4a) or tri-oxidation (to form M8c) in monkeys than in humans [358].…”
Section: Ring Openingmentioning
confidence: 99%
See 2 more Smart Citations
“…Vermier et al (2009) [358] recently extensively studied the metabolism of trabectedin in monkey and human liver microsomes. The authors found that the metabolite profiles of trabectedin at 5 M in Cynomolgus monkey and human liver microsomes were similar using 14 C-radiolabeled drug, although there was a higher abundance of the M4a/4b and M8b/8c metabolites in monkey fractions than in human fractions, suggesting a more active biotransformation of trabectedin via N-demethylation (to form M8b) and/or via demethylation with additional mono-oxidation (to form M4b), di-oxidation (to form M4a) or tri-oxidation (to form M8c) in monkeys than in humans [358].…”
Section: Ring Openingmentioning
confidence: 99%
“…M6a was the result of a combined demethylation and oxidation reaction at the A domain of the molecule, while M6b was likely the result from a demethylation and a mono-oxidation combined with a loss of two hydrogen atoms at the A domain of trabectedin. M8a was due to carboxylic acid formation at the A domain of the molecule; while M8b (ET-729) was formed by N-demethylation and M8c was likely the result of demethylation in combination with a triple oxidation, including an oxidation of the carbinolamine moiety to an amide, at the trabectedin A domain [358]. M9 was thought to be the result of an aliphatic ring opening at the methylene dioxybridge at the B subunit of trabectedin, whereas M16c was considered to be the result of an Odemethylation reaction at the C domain of trabectedin.…”
Section: Ring Openingmentioning
confidence: 99%
See 1 more Smart Citation
“…Trabectedin is extensively metabolized primarily through the CYP3A4 oxidative pathway, with lesser contributions from other CYP enzymes [47,48]. Fecal elimination is the primary route of excretion of trabectedin metabolites.…”
Section: Metabolism and Eliminationmentioning
confidence: 99%
“…Вследствие этого он пре-образуется во множество различных метаболитов. Ос-новные окислительные и деметилирующие изменения происходят в домене А. Домен С подвергается О-де-метилированию [9].…”
Section: Introductionunclassified